2018
DOI: 10.3389/fmicb.2017.02647
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Investigation of an Association of Induced Features and Corresponding Fungus during the Co-culture of Trametes versicolor and Ganoderma applanatum

Abstract: The co-culture of Trametes versicolor and Ganoderma applanatum is a model of intense basidiomycete interaction, which induces many newly synthesized or highly produced features. Currently, one of the major challenges is an identification of the origin of induced features during the co-culture. Herein, we report a 13C-dynamic labeling analysis used to determine an association of induced features and corresponding fungus even if the identities of metabolites were not available or almost nothing was known of bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…Previously silenced secondary metabolites are expressed in co-culture during stressful conditions, likely due to the activation of silent genes (Pettit, 2009; Schroeckh et al, 2009; Marmann et al, 2014; Li and Lou, 2017; Xu et al, 2018). Because Petri plates with nutrient agar produce a low yield, particularly when only a small portion of the plate has the chemistry of interest (i.e., the junction), a scale up study was conducted to enhance the amounts of secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously silenced secondary metabolites are expressed in co-culture during stressful conditions, likely due to the activation of silent genes (Pettit, 2009; Schroeckh et al, 2009; Marmann et al, 2014; Li and Lou, 2017; Xu et al, 2018). Because Petri plates with nutrient agar produce a low yield, particularly when only a small portion of the plate has the chemistry of interest (i.e., the junction), a scale up study was conducted to enhance the amounts of secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that only a fraction of the potential secondary metabolites are produced, likely due to fungal domestication as a result of repeated culturing at optimal media conditions. Another possibility is that the stressors that elicit the expression of certain secondary metabolites are not present (Keller, 2018; Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, chemical characterization of culture-specific metabolites was not possible since none matched known natural products. Identification of the source of metabolites in co-cultures also remains a major challenge, since the structure of such metabolites and other related biochemical information would be required (Xu et al, 2018). Nevertheless, we found that different cultures have variable impact on quorum sensing (Figure 6), such that metabolites obtained from co-cultures of the same fungus with two different bacteria clearly display contrasting effects on quorum sensing (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing attention is being paid to the metabolic effects of competitive interactions largely from the perspective of targeted assays of enzymes (Eyre et al 2010;Hiscox et al 2010a, b) and known secondary metabolites (Peiris et al 2008;Luo et al 2017). Initial investigations of changes in expression of the total metabolome in artificial media (Peiris et al 2008;Luo et al 2017;Xu et al 2018) and in wood (O'Leary 2018) as a result of ongoing interspecific interactions have been conducted. No attention has been paid however to any lasting effects that past competitive interactions might have on the metabolism of wood decaying fungi even though it is these effects that are likely to underpin on-going processes such as wood decomposition rate, community assembly trajectory and priority effects.…”
Section: Introductionmentioning
confidence: 99%